MODEL PEMBELAJARAN TEACHING FACTORY UNTUK MENINGKATKAN KOMPETENSI SISWA DALAM MATA PELAJARAN PRODUKTIF - Dadang Hidayat M. (Universitas Negeri Malang, 2011)
Abstract: The Model of Teaching Factory to Promote Students' Competence in Productive Subjects. The present article reports on a research project using the model of six-step teaching factory known as Model TF-6M. This R & D project was aimed at promoting students' competences regarding productive subjects at Vocational Schools. The six steps in the teaching factory model include receiving orders, analyzing orders, stating readiness in executing orders, execution of orders, doing quality control, and handing over products to customers. Prior to the implementation of the steps, the students and teachers made some agreements on the setting up of industrial atmosphere in the school, exercising communication skills, and exercising analysis of orders. The model was developed in the time blocks of six weeks in the fourth semester and six weeks in the fifth semester, which was subsequently followed with an exam on the competences. The results indicate that the model was effective in promoting students' productive competences. Abstrak: Model Pembelajaran Teaching Factory untuk Meningkatkan Kompetensi Siswa dalam Mata Pelajaran Produktif. Model teaching factory enam langkah adalah model pembelajaran hasil penelitian dengan menggunakan metode R&D. Model ini bertujuan meningkatkan kompetensi produktif siswa SMK. Enam langkah dari satu siklus model ini, yaitu menerima pemberi order, menganalisis order, menyatakan kesiapan mengerjakan order, mengerjakan order, melakukan quality control, dan menyerahkan order. Sebelum siklus model dilaksanakan, siswa dengan guru melakukan kesepakatan menciptakan iklim industri di sekolah, melakukan latihan berkomunikasi, dan berlatih menganalisis order. Model dilakukan dalam blok waktu enam minggu pada semester empat, enam minggu pada semester lima dan dilanjutkan dengan uji kompetensi. Hasil penelitian menunjukkan model ini efektif meningkatkan kompetensi produktif siswa.